Historical, Philosophical, and Contextual Values in Al-Wustho Mangkunegaran Mosque, Surakarta - Widyastuti Nurjayanti (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
Al-Wustho Mangkunegaran Mosque is one of the historical mosques in Surakarta, located in the Mangkunegaran Palace area. Kanjeng Gusti Pangeran Adipati Arya Mangkunegara-I initiated the construction. The mosque belongs to Mangkunegaran palace and is protected as a cultural heritage building. The purpose of this research is to find 1). the historical value of the building, 2). various philosophical values that underlie the shape/embodiment of the structure (spatial planning, building form, decorative arts), 3). contextual matters related to the function and condition of the Al-Wustho Mangkunegaran Mosque. The methods used are 1. historical plot tracing, building artifacts tracing through primary and secondary sources, 2. Interviews with mosque/marbot holders, community users, and community leaders. 3. Reference studies, analysis, and synthesis. The historical values are indicated by the existence of the palace mosque which is a cultural heritage building. The King besides being a ruler is also a religious leader (panatagama). The philosophical values are reflected in the design, construction, symbols, and ornamentation of mosques that contain Islamic philosophy. Located on a three-stack tajug roof, calligraphic ornamentation on gates, doors, windows, and columns is a reminder to be closer to Allah. The contextual values of the building are seen in the blending style of Javanese, European and Islamic cultures. The mosque also functions for the benefit of the people as the embodiment of rahmatan lil Alamin.